Augmented COlorimetric NANoplasmonic (CONAN) Method for Grading Purity and Determine Concentration of EV Microliter Volume Solutions - Zendrini, Andrea; Paolini, Lucia; Busatto, Sara; Radeghieri, Annalisa; Romano, Miriam; Wauben, Marca H. M.; van Herwijnen, Martijn J. C.; Nejsum, Peter; Borup, Anne; Ridolfi, Andrea; Montis, Costanza; Bergese, Paolo (Frontiers in Bioengineering and Biotechnology, 2020)
This protocol paper describes how to assign a purity grade and to subsequently titrate extracellular vesicle (EV) solutions of few microliters in volume by microplate COlorimetric NANoplasmonic assay (CONAN). CONAN assay consists of a solution of gold nanoparticles (AuNPs) into which the EV preparation is added. The solution turns blue if the EV preparation is pure, while stays red if soluble exogenous single and aggregated proteins, SAPs (often referred as protein contaminants) are present. The color change is visible by the naked eye or can be quantified by UV-Vis spectroscopy, providing an index of purity (a unique peculiarity up to date). The assay specifically targets SAPs, and not the EV related proteins, with a detection limit < 50 ng/µL (an order of magnitude higher resolution than the Bradford protein assay). For pure solutions, the assay also allows for determining the EV number, as the color shift is linearly dependent to the AuNP/EV molar ratio. Instead, it automatically reports if the solution bears SAP contaminants, thus avoiding counting artifacts. CONAN proves to be robust and reliable and also displays very interesting performances in terms of cost (inexpensive reagents, run by standard microplate readers), working volumes (1-2 µL of sample required) and time (full procedure takes less than one hour). The assay is applicable to all classes of natural and artificial lipid micro- and nanovesicles.